East blacktail 1 experimental site map - Johnston, Danielle; Wolf, Evan (Colorado State University. Libraries, 2016)
Experimental design map containing willow, well, exclosure, and velocity inhibitor locations at East Blacktail 1 monitoring site.
Zip file includes: map and read me file.
Natural Resource Ecology Laboratory (NREL)
Keywords: experimental design; browse exclosure; willow; beaver; monitoring well